Reduction and Separation of High Iron Content Manganese Ore and its Mechanism - Zhucheng Huang; Bin Chai; Lingyun Yi; Tao Jiang (The Minerals, Metals and Materials Society, 2013)
"A high iron content manganese ore was reduced at 900~1200°C and followed by a magnetic separation process. SEM and EDS analyzes were employed to examine the transformation of microstructure and phase in reduced sample and the mechanism was revealed. Results showed that elements enriched during reduction. Iron existed in the metal iron phase and most of oxygen formed compound with manganese. Consequently a clear distinguish between iron phase and manganese minerals formed, which was beneficial to the separation of iron and manganese. But the iron phase can not be monomer dissociation in grinding process and manganese compounds turned into magnetic product as package and mechanic inclusion due to the isomorphism of iron and manganese and the small particle size. And MnO could be found partially in iron phase, which hindered the further separation of manganese and iron.IntroductionManganese is widely used in industry. The amount of manganese used in steel industry is very huge and 90% manganese is used in steel industry. Manganese ore resources are rich in China, yet with fewer rich ore but more low-grade ore which accounts for 93.6% and fine refractory ore. The constitution of the ore is very complex and more than 73% of all the manganese ore contains iron[l,2]. With the increasing of consumption of steel, the demand for manganese is becoming larger and larger and the imported ore accounts for more than 50%. Therefore, how to use the manganese ore efficiently has very significant meaning. The main method is manganese residual, which is simple and stable. However, the development of the method is limited by the quality of manganese ore, the huge amount of manganese residual, the technology of blast furnace process and economics[3,4]. Chemical benefication which may pollute environment and is difficult to recover iron is still being researched[5,6]. The paper investigated the process in which anthracite coal was the reducing agent for coal-based direct reduction and magnetic separation of the ore, and SEM with EDS measurements were employed to examine the transformation of phase in reduced sample and the mechanism was revealed[7,8]."